Versatile optical determination of two-dimensional atomic crystal layers. (November 2016) - Ma, Bangjun; Wang, Peiqi; Ren, Shizhao; Jia, Chuancheng; Guo, Xuefeng
Abstract: An efficient method has been developed to facilitate the identification of the layer number of two-dimensional atomic crystals from their optical images. By analyzing the image contrasts of two-dimensional atomic crystals with different layers, such as graphene, hexagonal boron nitride (h-BN) and molybdenum disulfide (MoS2 ), on silicon substrates, it was found that the image contrasts of these two-dimensional materials showed the distinct relation with the layer number, which was well explained by the theoretical analysis. This method proved the importance of proper choices of the substrate to achieve a clear linear relation between the image contrast and the layer number. Since the method only relies on a standard optical microscope with a charge-coupled device (CCD) camera and simple calculation of the contrast from the optical images, the entire process of layer identification can be finished in a short time and with low cost, thus speeding up the exploration of the big family of two-dimensional atomic crystals.